THE PREVALENCE OF ELEVATED LEVELS OF C-REACTIVE PROTEIN AND ITS ASSOCIATION WITH TRADITIONAL RISK FACTORS AND MORBIDITY AMONG RESIDENTS OF THE RUSSIAN FEDERATION (ACCORDING TO THE ESSE-RF STUDY) - S. E. Evstifeeva; S. A. Shalnova; A. D. Deev; T. M. Gatagonova; A. Yu. Efanov; Yu. V. Zhernakova; V. A. Il'in; A. O. Konradi; V. A. Metelskaya; E. V. Oschchepkova; S. V. Romanchuk; O. P. Rotar; et al. (Столичная издательская компания, 2015)
Aim. To study the association of high-sensitivity C-reactive protein (hsCRP) level with socio-demographic, behavioral and traditional risk factors in different regions of the Russian Federation (RF). Material and methods. Data of the multicenter epidemiological study of cardiovascular disease in different regions of the Russian Federation (ESSE-RF) were used. Representative sample of the unorganized male and female population aged 25-64 from 6 regions of the Russian Federation was drown. 3407 men and 6354 women (n=9761) were included into the study. Standard questionnaire was applied in all subjects. Gender, age, level of education, place of residence and region of residence, traditional risk factors and diseases were analyzed. HsCRP level (level ≥3.0 mg/l was defined as elevated one) was evaluated to detect of indolent inflammation. Results. HsCRP levels in women was significantly higher compared to males (p<0.005). The average prevalence of elevated hsCRP in the regions was 24.2%, for men - 21.4%, and for women - 25.7% (p<0.005). Significant age-related dynamics of hsCRP (p<0.0001) was found. The average level of hsCRP was significantly lower (p<0.0001) in a cohort of persons with higher education against these with lower level of education. Level of hsCRP as well as prevalence of elevated hsCRP level were higher in villagers than this in the urban population (p<0.05). Prevalence of elevated hsCRP in patients with traditional risk factors after adjustment for sex, age, and region of residence showed that the elevated hsCRP was mostly associated with metabolic factors and diseases that were characterized by systemic inflammation. Conclusion. Elevated level of hsCRP (≥3.0 mg/l) was significantly associated with female gender, with an older, less educated, and smoking population of Russians. After the multivariate adjustment there remained significant associations (p<0.0001) of elevated hsCRP level with obesity, including abdominal obesity, hyperglycemia and hypertriglyceridemia, low levels of low density cholesterol, rheumatoid arthritis, chronic bronchitis and Parkinson's disease.